Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/acoustics1010018
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of the Stage Design to the Acoustics of Ancient Greek Theatres

Abstract: The famous acoustics of ancient Greek theatres rely on a successful combination of appropriate location and architectural design. The theatres of the ancient world effectively combine two contradictory requirements: large audience capacity and excellent aural and visual comfort. Despite serious alterations resulting from either Roman modifications or accumulated damage, most of these theatres are still theatrically and acoustically functional. Acoustic research has proven that ancient theatres are applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…There are speci c sounds, soundmarks and soundscapes that contribute to the cultural heritage of many localities and communities [147]. Such heritage soundscapes may also include internal acoustic environments of historical buildings [148], open-air sites of archaeological interest [149], and sounds associated with the fabric of historic memorials and locations [150]. From a heritage management perspective the diminishment or loss of these needs to be managed [35].…”
Section: What Covid-19 Can Tell Us About the Future Of Heritage Sounds?mentioning
confidence: 99%
“…There are speci c sounds, soundmarks and soundscapes that contribute to the cultural heritage of many localities and communities [147]. Such heritage soundscapes may also include internal acoustic environments of historical buildings [148], open-air sites of archaeological interest [149], and sounds associated with the fabric of historic memorials and locations [150]. From a heritage management perspective the diminishment or loss of these needs to be managed [35].…”
Section: What Covid-19 Can Tell Us About the Future Of Heritage Sounds?mentioning
confidence: 99%
“…In recent years, there has been a growing interest in the acoustical characterization of ancient open-air theatres, which led to the development of several research projects (see, e.g., in [1][2][3][4]) and a prolific production of scientific literature on the topic (see, e.g., in [5][6][7][8][9][10][11][12][13][14]). This reflects a general trend observable in the broader field of archaeoacoustics [15].…”
Section: Introductionmentioning
confidence: 99%
“…In this theatre, the value of Gm at 15 m is precisely +2 dB. As for the spatial parameters from Figure 7, JLF versus frequency presents low average values, as does (1-IACCE), although these lie within the typical range in non-occupied concert and multi-purpose halls of up to 25,000 m 3 . This last parameter shows a decrease in early lateral reflections at low and mid frequencies when the hill adjacent to the theatre is removed (Figure 7b).…”
Section: Resultsmentioning
confidence: 52%
“…In addition to the long-term interest by historians and archaeologists, increasing attention has been paid to the acoustic properties of ancient theatres in the last decade (acoustics is an immaterial aspect of space; acoustic heritage must be taken into account when reconstructing ancient theatres in accordance with the possible alternatives) [2]. Acoustic research on the theatres of the classical world has shown that these open-air performance venues demonstrate a successful combination of architectural design to harmonically accommodate a large audience and provide excellent visual and acoustic comfort [3].…”
Section: Introductionmentioning
confidence: 99%